Legal rights : the guide for deaf and hard of hearing people - National Association of the Deaf. (Washington, DC : Gallaudet University Press, 2015)
"This new, completely revised edition of Legal Rights: The Guide for Deaf and Hard of Hearing People meticulously describes the federal and state statutes that prohibit discrimination against deaf and hard of hearing people. Written in easy-to-understand language, the sixth edition explains critically important legislation such as the Rehabilitation Act of 1973, the Individuals with Disabilities Education Act (IDEA), and the Americans with Disabilities Act (ADA). It also includes the recent amendments to these laws -- the ADA Amendments Act (ADAAA) and new regulations to its Title II concerning public entities and Title III pertaining to public accommodations and commercial facilities; and the reauthorization of IDEA, which expanded the No Child Left Behind Act requirement of highly qualified teachers to include all students with disabilities. This updated edition of Legal Rights tracks the trend of passing a Deaf and Hard of Hearing Children's Bill of Rights in a growing number of state legislatures. It delineates new federal legislation such as the Twenty-First Century Communications and Video Accessibility Act, which ensures that deaf and hard of hearing people have access to the newest communications technology. Legal Rights also provides vital information on health care and social services, fair housing regulations, employment, and the use of interpreters in the legal system, securing its position as the most comprehensive source of legal information for deaf and hard of hearing people now available." -- Back cover.
Preface -- Acknowledgments -- Communicating with people who are deaf or hard of hearing -- The Americans with Disabilities Act -- The Rehabilitation Act of 1973 -- Public school education -- Postsecondary and continuing education -- Health care and social services -- Employment -- Housing -- The legal system -- Video media -- Telecommunication services -- Index.
Includes bibliographical references and index
Keywords: Deaf people -- Legal status, laws, etc. -- United States; Hard of hearing people -- Legal status, laws, etc. -- United States